SPIRITUALITY IN PATIENTS WITH ACUTE CORONARY SYNDROME (ACS): A LITERATURE REVIEW - Husnul Khotimah; Luthfiyyah Khanuun (JTH: Journal of Technology and Health, 2026)
Beyond its physical impact, Acute Coronary Syndrome (ACS) significantly disrupts a patient's psychological equilibrium. Incorporating spirituality into patient care offers a potential avenue for coping and facilitating holistic rehabilitation. This study synthesized current evidence regarding how spiritual factors and targeted spiritual care influence psychological and clinical outcomes in ACS cohorts. Following PRISMA 2020 protocols, a systematic search of PubMed, Scopus, and Google Scholar yielded 11 eligible original studies. Synthesis revealed that spiritual well-being strongly correlates with diminished levels of anxiety, existential dread, hopelessness, and PTSD symptoms, while concurrently fostering resilience, self-efficacy, and overall quality of life. Furthermore, structured spiritual care, family-integrated support, and dhikr-based therapies demonstrated clear psychological benefits. Consequently, integrating spiritual assessments into standard cardiovascular nursing practices is essential for comprehensive patient management.